A Thief in the Night: A Book of Raffles' Adventures - Hornung, E. W. (Ernest William), 1866-1921 (Salt Lake City, UT : Project Gutenberg, 2000)
"A Thief in the Night: A Book of Raffles' Adventures" by E. W. Hornung is a collection of short stories published in 1905. The third book featuring gentleman thief A. J. Raffles, it chronicles burglaries and close calls in late Victorian England, narrated by his accomplice Bunny Manders. The stories span different points in their criminal careers, from respectable gentlemen at the Albany to fugitives with ruined reputations, culminating in encounters with Scotland Yard and surprising revelations about Raffles's hidden acts of kindness. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Thief_in_the_Night_(short_story_collection)
Release date is 2000-03-01
Keywords: Raffles (Fictitious character) -- Fiction; Criminals -- England -- Fiction